A CRITICAL REVIEW OF LITERATURE IN THE RISING TIDE OF SOCIAL MEDIA TOWARDS PROMOTING TOURISM - Sin, Kit Yeng; Mohamad, Abang Azlan; Lo, May-Chiun (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
Information and Communications Technology (ICT) has been the focus of the tourism industry in recent decades, specifically for the travel and hospitality sector. The increase of usage and dependency on the Internet has escalated the growth of multiple forms and types of social channels, which have also transformed travel business for agencies and companies to communicate and market their services to the targeted demographics. Consumers would utilise the unlimited information from social media in deciding on potential destinations and leisure activities, which dramatically influences tourism marketing. Nonetheless, the interdisciplinary applications of digital platforms in the tourism industry have resulted in various studies that are found to be fragmented, resulting in gaps when translated into practice. Thus, a critical review of prior social media research is needed to interpret the precipitation and outcomes. Hence, this study had identified and synthesised 45 articles during 2012 to 2019 using extensive literature search within social media area of research interest within the field of tourism and hospitality Information System (IS). Contingent on a content analysis on the synthesised articles from both the individuals’ and firms’ perspectives, significant motivations, limitations, and conditional parameters of social media use were identified and categorised to develop a conceptual model holistically.